A novel ferrocene-containing aniline copolymer: its synthesis and electrochemical performance1. Issue 18 (5th March 2015) - Su, Chang; Ji, Lvlv; Xu, Lihuan; Zhu, Xiaogang; He, Huihui; Lv, Yaokang; Ouyang, Mi; Zhang, Cheng
<x xml:space="preserve">Abstract</x> The novel ferrocene-contained aniline based polymers were successfully synthesized, which demonstrated an improved discharge plateau at the potential range of about 3.0–4.0 V, as with the acceptable initial discharge specific capacity.